Spiking neural P systems: Recent results, research topics - Gheorghe Paun; Mario J. Pérez-Jiménez (Springer-Verlag, 2009)
After a quick introduction of spiking neural P systems (a class of P systems inspired from the way neurons communicate by means of spikes, electrical impulses of identical shape), and presentation of typical results (in general equiva- lence with Turing machines as number computing devices, but also other issues, such as the possibility of handling strings or infinite sequences), we present a long list of open problems and research topics in this area, also mentioning recent attempts to address some of them. The bibliography completes the information offered to the reader interested in this research area.
A. Condon, D. Harel, J.N. Kon, A. Salomaa, E. Winfree (eds)